In Quest of Peace and its Subject - Mosinyan, Davit (Conatus - Journal of Philosophy, 2023)
The dynamics of warfare have undergone significant transformations, necessitating a comprehensive reevaluation of the study of wars. It is no longer sufficient to solely focus on analyzing military operations; instead, a broader perspective is required. Postcolonial research has shed light on the changing forms of warfare that emerged after the era of military colonialism. This shift in the nature of conflicts demands the development and application of new research methods to effectively comprehend and address contemporary warfare. Of particular significance is the emergence of informational and hybrid warfare, which blurs the traditional boundaries between states of war and peace. Consequently, the concept of peace, as the desired state of coexistence, warrants closer examination from multidimensional angles. While peace has historically been considered from moral and religious viewpoints, it is imperative to critically evaluate the applicability of these perspectives and explore alternative approaches. This article seeks to unravel the complex nature of peace by integrating insights from diverse disciplines. By adopting a multidisciplinary approach, encompassing moral, religious, and other disciplinary lenses, a more comprehensive understanding of peace can be achieved. Moreover, this interdisciplinary exploration enables a nuanced analysis of the intricate dynamics between war and peace, facilitating the development of effective strategies for conflict resolution. By critically examining the concept of peace and reevaluating the nature of war from this perspective, this article aims to contribute to the existing body of knowledge on conflicts and their potential resolutions. By combining theoretical reflections with empirical evidence, it offers a valuable resource for researchers, policymakers, and practitioners interested in comprehending the complexities of contemporary conflicts and working towards the attainment and sustenance of lasting peace.